Effect of needle puncture and electro-acupuncture on mucociliary clearance in anesthetized quails - Wang Tianshan; Xutian Stevenson; Sun Feng; Wang Jiulin; Tai Shusheng; King Malcolm (BMC, 2006)
Abstract Background Acupuncture therapy for obstructive respiratory diseases has been effectively used in clinical practice and the acupuncture points or acupoints of Zhongfu and Tiantu are commonly-used acupoints to treat patients with the diseases. Since the impaired mucociliary clearance is among the most important features of airway inflammation in most obstructive respiratory diseases, the effect of needle puncture and electro-acupuncture at the specific acupoints on tracheal mucociliary clearance was investigated in anesthetized quails. Methods Mucociliary transport velocity on tracheal mucosa was measured through observing the optimal pathway, and fucose and protein contents in tracheal lavages were determined with biochemical methods. In the therapeutic group, needle puncture or electro-acupuncture stimulation to the acupoints was applied without or with constant current output in 2 mA and at frequency of 100 Hz for 60 minutes. In the sham group, electro-acupuncture stimulation to Liangmen was applied. Results Our present experiments demonstrated that the electro-acupuncture stimulation to Zhongfu and Tiantu significantly increased tracheal mucociliary transport velocity and decreased the content of protein in the tracheal lavage, compared with the control group. Moreover, either needle puncture or electro-acupuncture stimulation to Zhongfu and Tiantu significantly reverted the human neutrophil elastase-induced decrease in tracheal mucociliary transport velocity and human neutrophil elastase -induced increase in the contents of fucose and protein in the tracheal lavage, compared with the control group. Conclusion These results suggest that either needle puncture or electro-acupuncture stimulation to the effective acupoints significantly improves both airway mucociliary clearance and the airway surface liquid and that the improvements maybe ascribed to both the special function of the points and the substantial stimulation of electricity.